2022
DOI: 10.3390/jof8080883
|View full text |Cite
|
Sign up to set email alerts
|

Mycoremediation of Flotation Tailings with Agaricus bisporus

Abstract: Due to their enzymatic and bioaccumulation faculties the use of macromycetes for the decontamination of polluted matrices seems reasonable for bioremediation. For this reason, the aim of our study was to evaluate the mycoremediation ability of Agaricus bisporus cultivated on compost mixed with flotation tailings in different quantities (1, 5, 10, 15, and 20% addition). The biomass of the fruit bodies and the content of 51 major and trace elements were determined. Cultivation of A. bisporus in compost moderatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Additionally, agro-industrial wastes are used by mushrooms as substrates for growth and cultivation. Moreover, various fungal species of Penicillium, Rhizopus, Trichoderma, Aspergillus, Agaricus, and Pleurotus have manifested an association between toxic metal resistances and the capacity to reduce metal contamination from the wastewater [15,16]. For instance, Penicillium simplicissimum was found to tolerate 2000 mg L −1 Pb and 1000 mg L −1 Cu and it also showed removal efficiency of 16.18 and 38.98 mg g −1 from the liquid medium, respectively [15], whereas, Trichoderma asperellum displayed tolerance towards Cd, Cr, Cu, Pb, and Zn via the mechanism of biosorption [17].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, agro-industrial wastes are used by mushrooms as substrates for growth and cultivation. Moreover, various fungal species of Penicillium, Rhizopus, Trichoderma, Aspergillus, Agaricus, and Pleurotus have manifested an association between toxic metal resistances and the capacity to reduce metal contamination from the wastewater [15,16]. For instance, Penicillium simplicissimum was found to tolerate 2000 mg L −1 Pb and 1000 mg L −1 Cu and it also showed removal efficiency of 16.18 and 38.98 mg g −1 from the liquid medium, respectively [15], whereas, Trichoderma asperellum displayed tolerance towards Cd, Cr, Cu, Pb, and Zn via the mechanism of biosorption [17].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study show that the nanosilver clay composites are not indiscriminate and selectively inhibit the fungal pathogens, while not affecting the host fungus (A. bisporus), an observation that has also been shown in other studies where toxic trace elements, including silver, did not have any adverse effect on A. bisporus, either the mycelial growth or the production of fruiting bodies. [60] It was found that A. bisporus is highly selective in its accumulation of elements, a possible explanation for its insensitivity when growing in the presence of silver. In addition, A. bisporus is used to conduct extracellular synthesis of AgNPs, implying the presence of silver ion-reducing enzymes that could infer resistance to this metal.…”
Section: Effect Of Nanosilver Clay Composites On the Mycelial Growth ...mentioning
confidence: 99%
“…The fourth article describes a risk assessment of total mercury content in edible wild mushrooms in Slovakia, while the fifth article evaluates the concentration of six heavy metals in two edible oyster mushrooms [4,5]. Furthermore, the sixth article examines the mycomedial ability of Agaricus bisporus to grow on compost mixed with flotation residues [6]. The seventh article highlights the resistance of white and brown rot fungi to copper in the microcosm of copper/azole-treated wood [7].…”
mentioning
confidence: 99%